Simultaneous fault and input time delay estimation for an actuator system: theory and flight data validation - Chen, Lejun; Edwards, Christopher; Alwi, Halim; Sato, Masayuki (IEEE, 2021)
This paper proposes a first order sliding mode observer for the purpose of simultaneously estimating the unknown input time delay and reconstructing the loss of effectiveness in a model of an actuator. The adaptive algorithm is driven by the ‘equivalent output error injection’ signal associated with the sliding motion. Sufficient conditions are given to ensure finite time convergence of the state estimation error system, ensuring both the time delay estimation error and the estimation error associated with the actuator fault converge to a small region around zero. The efficacy of the approach has been evaluated via both a numerical simulation and flight data validation.
Keywords: Fault detection; Delay systems; Variable-structure/sliding-mode control